Natural endogenous ligands for benzodiazepine receptors in hepatic encephalopathy - Baraldi, M; Avallone, R; Corsi, L; Venturini, I; Baraldi, C; Zeneroli, M. L (Metabolic brain disease, 2009)
Benzodiazepines of natural origin (NBZDs) have been found in human blood and brains as well as in medicinal plants and foods. In plasma and brain tissue there are i.e. diazepam and nordiazepam equal to commercial drugs but there are also other benzodiazepine-like compounds termed “endozepines”, which act as agonists at the benzodiazepine receptors of central type (CBR). A synthetic pathway for the production of NBZDs has not yet been found, but it has been suggested that micro-organisms may synthesize molecules with benzodiazepine-like structures. Hence NBZDs could be of both endogenous and exogenous source and be considered as natural anxyolitic and sedative. Interestingly there are also natural compounds, such as the polypeptide Diazepam Binding Inhibitor (DBI) acting as an “inversive agonist” implicated in fair and panic disorders. It has been suggested that NBZDs may play a role in the pathogenesis of hepatic encephalopathy (HE). Multidirectional studies evaluated NBZDs levels (1) in the blood of normal subjects, of cirrhotic with or without HE and in commercial benzodiazepine consumers; (2) in the blood of cirrhotic treated or not with a non-absorbable antibiotic; (3) in several constituents of our diet. In conclusion, NBZDs increase sometime in cirrhotics with or without HE but they reach concentrations not higher than those found in commercial benzodiazepines consumers. Hence NBZDs must be considered as occasional precipitating factor of HE and benzodiazepine antagonists only symptomatic drugs. The finding that NBZDs may be in part synthesized by intestinal bacterial flora and in part constituent of our diet underlines the importance to feed cirrhotic patients with selected food.